TMPRSS2‐ERG fusions linked to prostate cancer racial health disparities: A focus on Africa. Issue 10 (15th May 2019) - Blackburn, James; Vecchiarelli, Stefano; Heyer, Erin E.; Patrick, Sean M.; Lyons, Ruth J.; Jaratlerdsiri, Weerachai; van Zyl, Smit; Bornman, M. S. Riana; Mercer, Tim R.; Hayes, Vanessa M.
Abstract: Background: The androgen‐regulated gene TMPRSS2 to the ETS transcription factor gene ERG fusion is the most common genomic alteration acquired during prostate tumorigenesis and biased toward men of European ancestry. In contrast, African American men present with more advanced disease, yet their tumors are less likely to acquire TMPRSS2‐ERG . Data for Africa is scarce. Methods: RNA was made available for genomic analyses from 181 prostate tissue biopsy cores from Black South African men, 94 with and 87 without pathological evidence for prostate cancer. Reverse transcription polymerase chain reaction was used to screen for the TMPRSS2‐ERG fusion, while transcript junction coordinates and isoform frequencies, including novel gene fusions, were determined using targeted RNA sequencing. Results: Here we report a frequency of 13% for TMPRSS2‐ERG in tumors from Black South Africans. Present in 12/94 positive versus 1/87 cancer negative prostate tissue cores, this suggests a 92.62% predictivity for a positive cancer diagnosis ( P  =   0.0031). At a frequency of almost half that reported for African Americans and roughly a quarter of that reported for men of European ancestry, acquisition of TMPRSS2‐ERG appears to be inversely associated with aggressive prostate cancer. Further support was provided by linking the presence of TMPRSS2‐ERG to low‐grade disease in younger patients ( P  =   0.0466), with higher expressing distal ERG fusion junction coordinates. Conclusions: Only the second study of its kind for the African continent, we support a link between TMPRSS2‐ERG status and prostate cancer racial health disparity beyond the borders of the United States. We call for urgent evaluation of androgen deprivation therapy within Africa.